Creation of independent educational platforms based on artificial intelligence - pcadmin, Ferangiz Jabborova Jahongir qizi (Academia One Publishing, 2025)
The rapid advancement of artificial intelligence (AI) has transformed various sectors, including education. Independent AI-based educational platforms provide learners with personalized experiences, adaptive learning paths, and real-time feedback, thereby enhancing the effectiveness of education. This article explores the development, implementation, and impact of AI-driven educational platforms. It discusses the current state of AI in education, the methodologies used in platform development, and the benefits and challenges associated with AI integration. Furthermore, recommendations for future advancements in AI-based education are provided.
Keywords: Artificial Intelligence; Adaptive Learning